NUMERICAL SOLUTION OF ISOTHERMAL GAS SPHERE PROBLEM - Guzel, Nuran; Oylumlu, Meseret Tuba (WORLD SCIENTIFIC PUBL CO PTE LTD, 2007)
In this paper, we use Pade approximation, to solve a boundary-value problem for an isothermal gas sphere, which is a special form of Lane-Emden equation. However, in general, the solution of Lane-Emden equation cannot be given analytically. This type of non-linear differential equations can be solved only numerically. An example is presented to show the ability of the method for Lane-Emden differential equation. Numerical solutions to the isothermal gas sphere have been discussed. We use MAPLE computer algebra systems for numerical calculations [Frank (1996)].
Keywords: Boundary-value problem for an isothermal gas sphere; Lane-Emden equations; power series; Pade approximation; MAPLE; Engineering; Mathematics